Synthesis, Anti-inflammatory and in silico Studies of few novel 1,2,4-Triazole Derived Schiff Base Compounds - Vishwakarma, Deepanshu; Gupta, Surya Prakash (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Every year more than 1 billion prescriptions are written for all NSAIDs and yet the quest to develop new NSAIDs remains prominent. Objectives: The current investigation's goal was to synthesize and assess the anti-inflammatory potential of a few more recent 1,2,4-triazole derivatives. Materials and Methods: The synthesis of the 1,2,4-triazole compounds (SPG1-5) was accomplished in three distinct steps involving formation of hydrazide of ibuprofen and followed by cyclization to 1,2,4-triazole nucleus and ultimately formation of Schiff’s base in the final step. Results: Each compound was dark brown in color and were obtained in 65-71% yields and was insoluble in water and hexane whereas SPG2 and SPG3 were soluble in methanol and all compounds were soluble in chloroform. The compounds were evaluated for in vitro anti-inflammatory potential utilizing albumin denaturation and inhibition of protease action methods. With SPG4 having the best ability to produce the inhibition (62.44±2.889%) at a concentration of 500 g/mL, all the substances showed dosage-dependent inhibition of albumin denaturation. SPG4 was able to inhibit protease activity (46.63±3.211%) at 500 g/mL and the antiprotease efficacy was also dosage-dependent. Conclusion: It was evident that the triazole derivatives were able to display moderate anti-inflammatory action and could be optimized to develop lead molecule.
Keywords: Triazole; Antiprotease; Anti-inflammatory; Albumin; in silico; in vitro